Conduct, Oversight, and Ethical Considerations of Clinical Trials in Companion Animals with Cancer: Report of a Workshop on Best Practice Recommendations. (7th March 2016) - Page, R.; Baneux, P.; Vail, D.; Duda, L.; Olson, P.; Anestidou, L.; Dybdal, N.; Golab, G.; Shelton, W.; Salgaller, M.; Hardy, C.
Abstract : Development of effective and safe treatments for companion animals with cancer requires the collaboration of numerous animal health professionals and the full engagement of animal owners. Establishing 'Best Practice Recommendations' for clinical trials in veterinary oncology represents an important step toward meeting the goal of rigorous clinical trial design and conduct that is required to establish valid evidence. Likewise, optimizing patient welfare and owner education and advocacy is crucial to meet the unique ethical obligations to both owners and animals enrolled in these clinical trials and to ensure trust in the team conducting the research. To date, 'Best Practice Recommendations' for clinical trial conduct have not been reported for veterinary oncology. This document summarizes the consensus of a workshop held in November, 2014 to identify relevant ethical principles and to ensure responsible conduct of clinical research in companion animals with cancer. It is intended as a working document that will be updated as advances in science and ethical considerations require. To the extent possible, existing guidelines for the conduct and oversight of clinical trials in humans have been adapted for veterinary trials to avoid duplicative effort and to facilitate integration of clinical trials such that translational research with benefits for both companion animals and humans are encouraged.